Analysis Of Water Content, Fiber, Anthocianin and Organoleptic Acceptance of Butterfly Pea Jelly Powder (Gatela) at Various Drying Temperatures Of Seaweed - Sukmawati, Novriza; Simanjuntak, Betty Yosephin; Wahyudi, Anang (Media Gizi Indonesia, 2024)
Jelly is a kind of food that consumers typically of all ages like. Food additive ingredients can increase the nutritional content while providing an attractive color to the food. Butterfly pea flowers have the potential to be developed as a local natural food colorant while providing antioxidant effects. This research aims to determine the organoleptic profile, water content, fiber and anthocyanin content of butterfly pea flower (Gatela) gelatin powder at various seaweed drying temperatures, carried out in February-March 2023. The treatments in the research were seaweed drying temperatures which were divided into 3, namely temperature 50°C, 60°C and 70°C. The initial stage is the preparation of the ingredients, then continued with making butterfly pea flower (Gatela) agar powder, as well as organoleptic testing. The best formulation is followed by analysis of water, fiber and anthocyanin content. This research involved 30 students as panelists with the parameters tested, namely color, aroma, texture and taste. The results of the organoleptic test showed that the selected butterfly pea flower (Gatela) agar powder was the most preferred, namely with a drying temperature of 50ºC in terms of aroma and texture. The results of the analysis on butterfly pea flower agar powder (Gatela) with a drying temperature of 50ºC were a water content of 12.18%, a fiber content of 4.93% and anthocyanin content of 154.84 ppm.